Immunomodulation with M2 macrophage–derived extracellular vesicles for enhanced titanium implant osseointegration under diabetic conditions - Yuzhao Cheng; Xin Dong; Jing Shi; Guangsheng Wu; Pei Tao; Nan Ren; Yimin Zhao; Fenglan Li; Zhongshan Wang (Materials Today Bio)
M2 macrophage–derived extracellular vesicles (M2-EVs) demonstrate the capacity to reduce pro-inflammatory M1 macrophage formation, thereby restoring the M1–M2 macrophage balance and promoting immunoregulation. However, the efficacy of M2-EVs in regulating macrophage polarization and subsequently enhancing osseointegration around titanium (Ti) implants in patients with diabetes mellitus (DM) remains to be elucidated. In this study, Ti implants were coated with polydopamine to facilitate M2-EVs adherence. In vitro experiment results demonstrated that M2-EVs could carry miR-23a-3p, inhibiting NOD-like receptor protein3(NLRP3) inflammasome activation in M1 macrophage and reducing the levels of inflammatory cytokines such as IL-1β by targeting NEK7. This improved the M1–M2 macrophage balance and enhanced mineralization on the Ti implant surfaces. The in vivo experiment results demonstrated that in diabetic conditions, the nanocoated M2-EVs significantly promoted high-quality bone deposition around the Ti implants. The current results provide a novel perspective for simple and effective decoration of M2-EVs on Ti implants; clinically, the method may afford osteoimmunomodulatory effects enhancing implant osseointegration in patients with DM.